The angel maker : a novel - North, Alex, 1976- (Celadon Books, a division of Macmillan Publishers, 2023)
"From the New York Times bestselling author of The Whisper Man and The Shadows comes a dark, suspenseful new thriller about the mysteries of fate, the unbreakable bond of siblings, and a notorious serial killer who was said to know the future. Growing up in a beautiful house in the English countryside, Katie Shaw lived a charmed life. At the cusp of graduation, she had big dreams, a devoted boyfriend, and a little brother she protected fiercely. Until the day a violent stranger changed the fate of her family forever. Years later, still unable to live down the guilt surrounding what happened to her brother, Chris, and now with a child of her own to protect, Katie struggles to separate the real threats from the imagined. Then she gets the phone call: Chris has gone missing and needs his big sister once more. Meanwhile, Detective Laurence Page is facing a particularly gruesome crime. A distinguished professor of fate and free will has been brutally murdered just hours after firing his staff. All the leads point back to two old cases: the gruesome attack on teenager Christopher Shaw, and the despicable crimes of a notorious serial killer who, legend had it, could see the future"--